"They have more than enough to do than patch up people like me." Experiences of seeking support for self‐harm in lockdown during the COVID‐19 pandemic. Issue 4 (24th April 2022) - Sass, Cara; Farley, Kate; Brennan, Cathy
Accessible Summary: What is known on the subject?: In the initial months of the pandemic, there was no significant increase in demand for mental health services During the pandemic, there was an increase in people reporting an increase in suicidal thoughts. Understanding of the experience of seeking help for self‐harm during lockdown is lacking, in terms of availability and accessibility of support services What the paper adds to existing knowledge?: People who self‐harm found that their support structures were significantly impacted by lockdown Lockdown presented relational difficulties for people who self‐harm What are the implications for practice?: Learning about the experience of receiving support from mental health liaison services during lockdown from a first‐hand perspective is essential to improving the provision of these services in the future. In times of national crisis, services should be prepared to support clients via alternative means including telephone and online. Public facing messages about service availability should be carefully expressed to minimize misunderstandings. Abstract: Introduction: National lockdown caused disruption to health services and third‐sector organizations offering support to people who self‐harm. Early reports suggested self‐harm‐related hospital attendances declined. Lack of knowledge related to the availability and accessibility of support provisions for people who self‐harm warrants exploration into how they experienced help‐seeking during lockdown. Aims: This study aimed to explore the experiences of people who self‐harm and perspectives on help‐seeking. Method: We conducted a qualitative study based on telephone and email interviews with 14 people who self‐harm in England. Results: Participants identified challenges to coping with life in lockdown, emphasizing the role of self‐harm. Help‐seeking was impeded by feeling like a burden and potential for spreading the virus. People who self‐harm exercised self‐reliance in response to "stay home" messaging, but some may have struggled without formal support. Online support served an important role in continuity of care during lockdown but could widen inequalities from limited resources and access. Implications for practice: Helping mental health liaison nurses to understand the experiences of people who self‐harm during lockdown is critical to providing continuing support to this population. Services should consider how and when they communicate changes to their provisions to the public, and the impact this will have on those in need of support.